2020
DOI: 10.29333/iji.2020.13159a
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Self-Regulation Skills through Group Investigation Integrated with Think Talk Write

Abstract: This study aims to (1) determine the difference between the improvement in students' self-regulation skills before and after the implementation of the GITTW learning strategy, and (2) describe students' perception of the skills of selfregulation before and after the implementation of the GITTW learning strategy. This is pre-experimental research using a one-group pre-test-post-test design. The population was made up entirely of students in their sixth semester at the Biology Education department who programmed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…Sawalhah and Al-Zoubi (2020) affirmed that self-regulation is one of the most important things that help the learner to improve their level on the one hand, and on the other hand, it works to improve self-esteem and appreciation and develops motivation that directs behavior towards specific goals in order to reach the best levels of academic performance and gain information and skills. Listiana et al (2020) confirmed that self-regulation is a proactive process organized by students who manage their thinking and behavior so as to achieve satisfaction and stability. Thus, it can be concluded that social intelligence can be predicted through self-regulation.…”
Section: Results Regarding Testing the Third Hypothesismentioning
confidence: 76%
See 1 more Smart Citation
“…Sawalhah and Al-Zoubi (2020) affirmed that self-regulation is one of the most important things that help the learner to improve their level on the one hand, and on the other hand, it works to improve self-esteem and appreciation and develops motivation that directs behavior towards specific goals in order to reach the best levels of academic performance and gain information and skills. Listiana et al (2020) confirmed that self-regulation is a proactive process organized by students who manage their thinking and behavior so as to achieve satisfaction and stability. Thus, it can be concluded that social intelligence can be predicted through self-regulation.…”
Section: Results Regarding Testing the Third Hypothesismentioning
confidence: 76%
“…Webb et al (2018) referred to self-regulation as the control mechanism that enables the student to manage attention, emotion, behavior, and perception to participate in goal-oriented actions. Besides, Park et al (2019) indicated that selfregulation is the cognitive, behavioral and emotional skills that allow individuals to work efficiently towards achieving their desired goals, especially when they are under stress Listiana et al (2020) argued that self-regulation includes the skills of time management, planning and managing strategies, and perseverance in completing difficult tasks. These skills increase the individual's ability to learn and can be improved and developed through training.…”
Section: Self-regulationmentioning
confidence: 99%
“…Rustiana et al, (2021) explain using the TTW model with a learning syntax starting from planning, thinking, considering, testing, and finally pouring ideas that can be used to solve problems faced by students so that students are accustomed to practicing critical thinking skills. In line with this Wahyuni & Efuansyah., (2018); Supandi et al, (2018); Listiana et al, (2020) by applying the TTW learning model students can construct conceptual understanding to train critical thinking by carrying out a reasoning approach which later on understanding the results of the reasoning will be poured into the form of ideas which will then be communicated to others and collaborated on the results of these ideas.…”
Section: Introductionmentioning
confidence: 99%
“…This is because in its implementation, science learning provides opportunities to grow analytical, inductive and deductive thinking skills to solve problems related to natural events around. In particular, the role of Biology in everyday life is very important, not only theoretically mastering concepts but also in their application and attachment to other sciences (Kusumastuti et al, 2019;Listiana, 2020;Pertiwi et al, 2018).…”
Section: A Introductionmentioning
confidence: 99%